Thermal Elastic Mechanics Problems of Concrete Rectangular Thin Plate - Cheng, Xuansheng (Springer Tracts in Civil Engineering ,, 2018)
This book discusses the thermal-elastic mechanics problems of concrete rectangular thin plate. Using theoretical derivation combined with numerical examples, it explains in detail the analytical solution of the deflection, bending moment, thermal vibration and thermal buckling of concrete rectangular thin plate. To facilitate application, the book also includes deflection and bending moment calculation tables of concrete rectangular thin plate with four edges supported and with free boundary conditions.